On characterizations of real hypersurfaces in a complex space form with n-parallel shape operator - Kon, S.H.; Loo, T.H. (2008)
In this paper, we study real hypersurfaces in a non-flat complex space form with n-parallel shape operator. Several partial characterizations of these real of these real hypersurfaces are obtained.